Tissue-resident memory CD8+ T cells amplify anti-tumor immunity by triggering antigen spreading through dendritic cells - Evelyn Menares (Nature Portfolio, 2019)
Immunotherapy can induce antigen spreading of antitumor T cell response, which correlates with better outcomes. Here the authors show that tissue-resident memory CD8 T cells promote antigen spreading via lysing tumor cells and promoting their uptake and cross-presentation by dendritic cells, thereby eliciting de novo T cell responses.